Regulatory Modules of Metabolites and Protein Phosphorylation in Arabidopsis Genotypes With Altered Sucrose Allocation - Stefan, Thorsten; Wu, Xu Na; Zhang, Youjun; Fernie, Alisdair; Schulze, Waltraud X. (Frontiers in Plant Science, 2022)
Multi-Omics data sets are increasingly being used for interpretation of cellular processes in response to environmental cues. Especially the posttranslational modification of proteins by phosphorylation is an important regulatory process affecting protein activity and/or localization, which in turn can have effects on metabolic processes and metabolite levels. Despite this importance, the relationships between protein phosphorylation status and metabolite abundances remains largely underexplored. Here, we used a phosphoproteomics – metabolomics data set collected at the end of day and night in shoots and roots of Arabidopsis to propose regulatory relationships between protein phosphorylation and accumulation or allocation of metabolites. For this purpose, we introduced a novel, robust co-expression measure suited to the structure of our data sets, and we used this measure to construct metabolite-phosphopeptide networks. These networks were compared between wild type and plants with perturbations in key processes of sugar metabolism, namely sucrose export (sweet11/12 mutant) or starch synthesis (pgm mutant). The phosphopeptide – metabolite network turned out to be highly sensitive to perturbations in sugar metabolism. Specifically, KING1, the regulatory subunit of SnRK1, was identified as a primary candidate connecting protein phosphorylation status with metabolism. We additionally identified strong changes in the fatty acid network in the sweet11/12 mutant, potentially resulting from a combination of fatty acid signaling and metabolic overflow reactions in response to high internal sucrose concentrations. Our results further suggest a substantial number of novel protein-metabolite relationships as candidates for future targeted research.